Challenges and limitations in developing of a new maxillary standardized rat alveolar bone defect model to study bone regenerative approaches in oral and maxillofacial surgery - Ahmed Omar, Naïma; Roque, Jéssica; Bergeaut, Céline; Bidault, Laurent; Amédée, Joëlle; Letourneur, Didier; Fricain, Jean-Christophe; Fenelon, Mathilde (Frontiers in Bioengineering and Biotechnology, 2025)
Innovative biomaterials are increasingly being investigated for guided bone regeneration (GBR) in oral and maxillofacial surgery. However, the development of relevant preclinical models still need to be consiedered. This study aimed to propose a standardized and reproducible maxillary bone defect model in rats that could be relevant to evaluate new materials for GBR. Three defect sizes in rat maxillary of 2.8, 3.3, and 4.5 mm in diameter were compared. Bone formation was followed until 12 weeks post-surgery using longitudinal micro-computed tomography and histological analysis. The defect was subsequently filled by an osteoconductive bone substitute (GLYCOBONE), then covered either by a new natural polysaccharide membrane supplemented with hydroxyapatite, or by a commercial collagen membrane (BIO-GIDE). Results showed little spontaneous tissue regeneration for empty defects (bone volume fractions (BVF) below 40% after 12 weeks). The smallest size defect (2.8 mm) was the most reproducible and was thus selected for testing GBR membranes. Defects filled with GLYCOBONE and covered with membranes displayed for both materials accelerated and substantial bone regeneration (with BVF that reached 80% after 12 weeks). Histological sections showed immature bone formation for the empty defects, whereas the defects filled with the GBR membranes highlighted a lamellar structured bone. The polysaccharide membrane was as effective as the commercial collagen membrane to guide bone tissue regeneration. This study provides a step-by-step protocol of a new standardized rat maxillary bone defect model. In line with ethical and financial considerations, this rodent model should be considered as a preliminary level before performing larger animal experiments.